Labour Market Outcomes for Cancer Survivors: A Review of the Reviews - Adelina Sharipova; Stijn Baert (Global Labor Organization (GLO), 2019)
Objectives: To synthesise the existing reviews conducted on the labour market outcomes of cancer survivors by focusing on (i) the convergences and divergences on the overall work-related outcomes, (ii) the moderating factors studied to date, and (iii) an identification of areas where more research is needed in the future. Methods: A systematic review of the existing reviews on labour market outcomes for cancer survivors was performed. Bibliographic search for eligible studies published before January 2019 involved the following three core concepts: (i) cancer survivors, (ii) work, and (iii) review. The quality of the included reviews was assessed based on the Johns Hopkins Hospital Evidence Level and Quality Guide. Following this, a narrative synthesis of the findings was completed. Results: In total, 35 articles met the inclusion criteria. The average return to work (RTW) rate varied between 54% and 66%. The self-reported work ability was consistently lower following cancer. This review also found strong converging evidence of self-reported discrimination after cancer. The effects on work performance showed several inconsistencies, possibly due to the use of different definitions of work performance. Most moderating factors for successful work outcomes showed converging evidence, except for age, marital status, cancer type, and country. We provide several possible explanations and linkages for these divergencies. Conclusions: Further investigation of causal relationships by (i) using matched control groups and by (ii) gathering longitudinal data, and the use of more standardised definitions of the outcome variables are the two main future research recommendations. Furthermore, no studies have succeeded in measuring the work outcomes objectively. We provide specific recommendations from an interdisciplinary context to solve this.
Keywords: 330; labour market outcomes; employment; return to work; cancer survivorship; review of reviews; research overview